x 3 y 3 = (x y)(x 2 xy y 2 ) this formula can be derived from (x y) 3 = x 3 y 3 3xy(x y) x 3 y 3 = (x y) 3 3xy(x y) x 3 y 3 = (x y)(xThe following are algebraix expansion formulae of selected polynomials Algebra Expansion Formulae, Mathematics Mathematics Menu (x y) 3 = x 3 3x 2 y 3xy 2 y 3 Difference of two cubes x 3 y 3 = (x y) (x 2 xy y 2) Link to this Webpage Copy Text to clipboard Click for Suggested CitationX y is a binomial in which x and y are two terms In mathematics, the cube of sum of two terms is expressed as the cube of binomial x y It is read as x plus y whole cube It is mainly used in mathematics as a formula for expanding cube of sum of any two terms in their terms ( x y) 3 = x 3 y 3 3 x 2 y 3 x y 2
Tourmaline General Formula Xy 3 Z 6bo 33